Control of the spatial homogeneity of pore surface chemistry in particulate activated carbon. (December 2015) - Sedghi, Saeid; Madani, S. Hadi; Hu, Cheng; Silvestre-Albero, Ana; Skinner, William; Kwong, Philip; Pendleton, Phillip; Smernik, Ronald J.; Rodríguez-Reinoso, Francisco; Biggs, Mark J.
Abstract: We show here that a physical activation process that is diffusion-controlled yields an activated carbon whose chemistry – both elemental and functional – varies radially through the particles. For the ∼100 μm particles considered here, diffusion-controlled activation in CO2 at 800 °C saw a halving in the oxygen concentration from the particle periphery to its center. It was also observed that this activation process leads to an increase in keto and quinone groups from the particle periphery towards the center and the inverse for other carbonyls as well as ether and hydroxyl groups, suggesting the two are formed under CO2 -poor and -rich environments, respectively. In contrast to these observations, use of physical activation processes where diffusion-control is absent are shown to yield carbons whose chemistry is radially invariant. This suggests that a non-diffusion limited activation processes should be used if the performance of a carbon is dependent on having a specific optimal pore surface chemical composition.